Development of a District‐Level Programmatic Assessment Tool for Risk of Measles Virus Transmission. Issue 6 (15th May 2015) - Lam, Eugene; Schluter, W. William; Masresha, Balcha G.; Teleb, Nadia; Bravo‐Alcántara, Pamela; Shefer, Abigail; Jankovic, Dragan; McFarland, Jeffrey; Elfakki, Eltayeb; Takashima, Yoshihiro; Perry, Robert T.; Dabbagh, Alya J.; et al.
Abstract : All six World Health Organization (WHO) regions have now set goals for measles elimination by or before 2020. To prioritize measles elimination efforts and use available resources efficiently, there is a need to identify at‐risk areas that are offtrack from meeting performance targets and require strengthening of programmatic efforts. This article describes the development of a WHO measles programmatic risk assessment tool to be used for monitoring, guiding, and sustaining measles elimination efforts at the subnational level. We outline the tool development process; the tool specifications and requirements for data inputs; the framework of risk categories, indicators, and scoring; and the risk category assignment. Overall risk was assessed as a function of indicator scores that fall into four main categories: population immunity, surveillance quality, program performance, and threat assessment. On the basis of the overall score, the tool assigns each district a risk of either low, medium, high, or very high. The cut‐off criteria for the risk assignment categories were based on the distribution of scores from all possible combinations of individual indicator cutoffs. The results may be used for advocacy to communicate risk to policymakers, mobilize resources for corrective actions, manage population immunity, and prioritize programmatic activities. Ongoing evaluation of indicators will be needed to evaluate programmatic performance and plan risk mitigation activities effectively. The availability of a comprehensive tool that can identify at‐risk districts will enhance efforts to prioritize resources and implement strategies for achieving the Global Vaccine Action Plan goals for measles elimination.